Teaching students to critically read digital images: a visual literacy approach using the DIG method. Issue 1 (3rd April 2019) - Thompson, Dana Statton
Abstract: This innovative teaching idea, the Digital Image Guide (DIG) Method, addresses the pressing need to develop visual pedagogies in the university classroom by providing a technique for students to use to critically read digital images. This article also introduces the concept of shallow and deep images . It then explains the difference between the two types of images and how to use the DIG Method to dig deeper in order to understand deep images . By utilizing the DIG Method, students can learn to analyze, interpret, evaluate and comprehend images found on social media sites and around the web, increasing their visual literacy skills in the process.